Association of Iron Deficiency Anemia with Maternal Psychological DistressDuring Pregnancy - Qureshi, Samaa; Haroon, Zujaja Hina; Khan, Muhammad Qaiser Alam; Munir, Muhammad Usman; Younas, Muhammad; Anwar, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To establish an association between iron deficiency anemia and maternal psychological distress during pregnancy.Study Design: Cross-sectional study.Place and Duration of Study: Chemical Pathology & Endocrinology department of Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from July to December 2022.Methodology: A total of 131 individuals were categorized into iron deficiency anemia (IDA) Group (n = 51) and non-IDA Group with normal pregnant females or those having anemias of etiology other than iron deficiency (n = 80) using a non-probability convenient sampling technique. The risk of psychological distress was measured by a scale adopted from Depression Anxiety Stress Scale 21.Results: Antenatal depression, anxiety and stress in IDA as compared to non-IDA Group (86.3 % vs 43.8 %, 84.3 % vs 51.2 %, and 91.1 % vs 66.3 %) showed significant difference (< 0.001) respectively. There was a significant negative correlation (r) of depression (r = -0.32), anxiety (r = -0.40), and stress (r = -0.37) with the serum ferritin levels (p=